Digital Archives and Preservation of Zakat-related Documents: Towards a Comprehensive Resource for Islamic Philanthropy - Nayak, Venkatesha; Hegde, Kavya P (Proceedings of International Conference on Islamic Civilization and Humanities, 2023)
The purpose of this study is to propose a framework for the digital archiving and preservation of zakat-related documents within the context of Islamic philanthropy. Methodology involving literature review and analysis, this research explores the theoretical and practical aspects of creating a comprehensive digital archive. The findings reveal the importance of digital technologies in preserving and providing accessibility to zakat-related materials, while considering factors such as digitization methods, metadata standards, and long-term preservation strategies. The study contributes to the fields of Islamic studies and digital humanities by enhancing the scholarly understanding of zakat and Islamic philanthropy and providing a valuable resource for researchers and the general public. This research emphasizes the need for comprehensive digital preservation practices to ensure the long-term availability and utilization of zakat-related documents.